Experimental study of free-surface fluctuations in open-channel flow in the presence of periodic cylinder arrays - Zhao, Kuifeng (2014)
The presence of periodic cylinder arrays in a laboratory-scale open-channel flow may induce significant fluctuations in the free-surface elevation. Experimental observations show four types of free-surface patterns, which include plane surface, transversely oscillating surface, longitudinally oscillating surface, and locally disturbed surface. The transversely oscillating surface appears to be standing waves confined between the two sidewalls in the flume and is well described by velocity potential equations. By considering the effect of the cylinder density, a modified dispersion equation is used to compute the frequency of the standing waves. The computed results agree well with the measured dominant frequency especially for cases with higher cylinder density, in comparison with those calculated using the equation without considering the effect of cylinder density. The data analysis also shows that the fluctuation in the free-surface elevation varies with flow conditions, and the maximum fluctuation occurs when the cylinder-diameter-based Reynolds number varies in the range of 600–800 or the cylinder-diameter-based Froude number varies in the range of 0.24–0.32.